Sequencing at the syllabic and supra-syllabic levels during speech perception: an fMRI study - Deschamps, Isabelle; Tremblay, Pascale (Frontiers in Human Neuroscience, 2014)
The processing of fluent speech involves complex computational steps that begin with the segmentation of the continuous flow of speech sounds into syllables and words. One question that naturally arises pertains to the type of syllabic information that speech processes act upon. Here, we used functional magnetic resonance imaging to profile regions, using a combination of whole-brain and exploratory anatomical region-of-interest (ROI) approaches, that were sensitive to syllabic information during speech perception by parametrically manipulating syllabic complexity along two dimensions: (1) individual syllable complexity, and (2) sequence complexity (supra-syllabic). We manipulated the complexity of the syllable by using the simplest syllable template—a consonant and vowel (CV)-and inserting an additional consonant to create a complex onset (CCV). The supra-syllabic complexity was manipulated by creating sequences composed of the same syllable repeated 6 times (e.g. /pa-pa-pa-pa-pa-pa/) and sequences of 3 different syllables each repeated twice (e.g. /pa-ta-ka-pa-ta-ka/). This parametrical design allowed us to identify brain regions sensitive to (1) syllabic complexity independent of supra-syllabic complexity, (2) supra-syllabic complexity independent of syllabic complexity and, (3) both syllabic and supra-syllabic complexity. High-resolution scans were acquired for 15 healthy adults. An exploratory anatomical ROI analysis of the supratemporal plane (STP) identified bilateral regions within the anterior two-third of the planum temporale, the primary auditory cortices as well as the anterior two-third of the superior temporal gyrus that showed different patterns of sensitivity to syllabic and supra-syllabic information. These findings demonstrate that during passive listening of syllable sequences, sublexical information is processed automatically, and sensitivity to syllabic and supra-syllabic information is localized almost exclusively within the STP.